Timing of trenbolone acetate implants on performance, carcass characteristics, and beef quality of finishing steer calves - G. L. Huck; Robert T. Brandt Jr.; D.D. Simms; Gerry L. Kuhl; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1991)
Angus and Angus-cross calves (632 lb) were utilized in a finishing study to evaluate the effects of implanting with estradiol and progesterone (Synovex-S®) and(or) trenbolone acetate (Finaplix®) on performance of finishing steers. Over the entire finishing period (117 d), implanted steers had higher (P<.05) daily gains and were more efficient than nonimplanted steers. Carcasses from implanted cattle had heavier (P<.05) hot weights and larger (P<.05) ribeye areas. Steers implanted with Finaplix had larger (P<.05) ribeye areas than those implanted with Synovex only. Marbling scores and quality grades were not affected by implant treatments. Rib (9-10-11) sections from implanted steers were heavier (P<.05) as a result of both heavier (P<.05) bone and soft tissue weights. However, no differences in percentages of protein, fat, and moisture were detected by proximate analysis of the soft tissue. Concomitant use of Finaplix with Synovex-S did not affect performance of Angus and Anguscrossed steer calves.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Trenbolone acetate; Performance; Carcass traits; Chemical composition